One Faith No Longer : The Transformation of Christianity in Red and Blue America - Yancey, George A., 1962-; Quosigk, Ashlee (Book collections on Project MUSE., 2021)
"This book investigates how conservative and progressive Christians use their political attitudes and theological beliefs to define their social outgroups and shape their social identities. The core question is the role political and theological values play in the construction of the social identities of conservative and progressive Christians and how those values help members of each group find answers to questions of meaning. The bottom line the authors seek to illuminate in this book is that Progressive and Conservative Christians use entirely different factors in determining their social identity and moral values and we articulate ways in which they differ. The authors utilize a mixed methods approach to explore this question. They highlight how Progressive Christians, whom rely on what we call a Humanistic Ethic of Social Justice, emphasize political values relating to social justice issues as they determine who is part of their in-group, and tend to be less concerned about theological agreement. Conservative Christians, on the other hand, rely on a historical theology emphasizing biblical doctrines, and do not put strong emphasis on political agreement as they determine if you are one of them-their major concern is whether you agree with them on core theological points. This helps answer the question about the nature of the theological divide within Christianity and the degree to which this disagreement leads to distinctive religious groups. Indeed, the authors argue that the way these two groups deal with questions of meaning are so opposed that it is time to regard them as distinct religious groups rather than subgroups under a single religious umbrella. By examining the data, the authors argue that the divide between theologically progressive and conservative Christians is so great that one can realistically think of them as different religious groups"--